Upaya Meningkatkan Hasil Belajar Bahasa Indonesia Melalui Penerapan Teknik Membaca Intensif - Rama Naibaho (JURNAL GLOBAL EDUKASI, 2021)
Abstract: The purpose of this study was to find out that there was an increase in student learning outcomes in the material Concluding Expositional Text Contents (Main idea) from Various Induction Paragraph Patterns, Deduction through the Application of Intensive Reading Techniques in class VIII students of SMP Negeri 3 Muara in the 2019/2020 academic year. The research subjects were 32 students of class VIII, while the research object was the improvement of student activity and learning outcomes in Indonesian language learning. This study's results indicate the average value of student learning outcomes in the first cycle of 65.94, then the number of students who completed was 18 students (56.25%). From the point of view of student motivation in the first cycle, it was obtained from 32 students, 18 students completed their studies (56.25%) seen from their learning motivation. The average student learning outcomes in the second cycle was 72.50, then the number of students who completed was 30 students (93.75%). The student motivation point in the first cycle was obtained from 32 students who completed their learning or 100%. It can be concluded that there is an increase in student results on the material Concluding the Contents of Exposition Text (Main idea) from Various Induction Paragraph Patterns, Deduction through the Application of Intensive Reading Techniques in Class VIII Students of SMP Negeri 3 Muara in the 2019/2020 Academic Year. Keyword: intensive reading; learning outcomes; main ideas; motivation Abstrak: Tujuan penelitian ini adalah mengetahui ada peningkatkan hasil belajar siswa pada materi Menyimpulkan Isi Teks Eksposisi (Ide pokok) Dari Berbagai Pola Paragraf Induksi, Deduksi Melalui Penerapan Teknik Membaca Intensif pada siswa kelas VIII SMP Negeri 3 Muara Tahun Pelajaran 2019/2020. Subjek penelitian adalah siswa kelas VIII sebanyak 32 siswa sedangkan yang menjadi objek penelitian adalah peningkatan keaktifan dan hasil belajar siswa pada pembelajaran Bahasa Indonesia. Hasil penelitian ini menunjukkan nilai rata-rata hasil belajar siswa pada siklus pertama sebesar 65,94 kemudian jumlah siswa yang tuntas sebanyak 18 siswa (56,25%). Dari sudut motivasi belajar siswa pada siklus I diperoleh dari 32 siswa terdapat 18 orang yang tuntas belajarnya (56,25%) dilihat dari motivasi belajarnya. Rata-rata hasil belajar siswa pada siklus II sebesar 72,50 kemudian jumlah siswa yang tuntas sebanyak 30 siswa (93,75%). Dari sudut motivasi belajar siswa pada siklus I I diperoleh dari 32 siswa yang tuntas belajarnya atau 100%. dAPAT disimpulkan ada peningkatkan hasil siswa pada materi Menyimpulkan Isi Teks Eksposisi (Ide pokok) Dari Berbagai Pola Paragraf Induksi, Deduksi Melalui Penerapan Teknik Membaca Intensif Pada Siswa Kelas VIII SMP Negeri 3 Muara Tahun Pelajaran 2019/2020. Kata Kunci: membaca intensif, ide pokok, motivasi, hasil belajar